2017
DOI: 10.3390/ijms18030665
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Unfolded Protein Response in Cartilage Pathophysiology; Contributing Factors to Apoptosis and Osteoarthritis

Abstract: Chondrocytes of the growth plate undergo apoptosis during the process of endochondral ossification, as well as during the progression of osteoarthritis. Although the regulation of this process is not completely understood, alterations in the precisely orchestrated programmed cell death during development can have catastrophic results, as exemplified by several chondrodystrophies which are frequently accompanied by early onset osteoarthritis. Understanding the mechanisms that underlie chondrocyte apoptosis duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 113 publications
(144 reference statements)
1
64
0
Order By: Relevance
“…It is possible that conjugation of Ufm1 to Ddrgk1 protects it during ER stress and Ddrgk1 in turn stabilizes other proteins like Sox9 however further studies are needed to determine this. Many chondrodysplasias result from the inability of chondrocytes or osteoblasts to deal with increasing load in the ER, be it due to mutations in the ER machinery or mutations of ECM structural proteins resulting in their misfolding [16]. Many affected by these disorders develop OA as a secondary consequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that conjugation of Ufm1 to Ddrgk1 protects it during ER stress and Ddrgk1 in turn stabilizes other proteins like Sox9 however further studies are needed to determine this. Many chondrodysplasias result from the inability of chondrocytes or osteoblasts to deal with increasing load in the ER, be it due to mutations in the ER machinery or mutations of ECM structural proteins resulting in their misfolding [16]. Many affected by these disorders develop OA as a secondary consequence.…”
Section: Discussionmentioning
confidence: 99%
“…The relative expression of Runx2, Osterix, Osteocalcin and Col1a1 were measured in the 2T3 culture system as the markers of osteogenic differentiation [7]. Bip expression was also measured as its expression is known to increase during osteogenic differentiation as well as during ER stress [6]. We found that Ufsp2, Uba5 (E1), Ufl1 (E3), Ddrgk1 and Lzap were all significantly upregulated in the induced cultures relative to the control at day 8.…”
Section: Ufm1 System and Osteogenic Differentiationmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, loss of function mutations in PERK, one of the sensors of ER stress, underlie the multiple abnormalities seen in patients with Wolcott‐Rallison syndrome, including short stature, low bone mass, neuromotor defects, hepatic and renal failure secondary to early‐onset diabetes mellitus . Skeletal disease often involves alterations in redox status, hypoxia, and other factors that could alter protein folding . These conditions could induce ER stress and the UPR in bone cells, particularly matrix synthesizing osteoblasts, and osteocytes, which secrete a variety of factors, involved in control of bone formation and resorption .…”
Section: Introductionmentioning
confidence: 99%
“…The cellular response mechanisms that underlie intrinsic cartilage and subchondral bone repair after joint injury are poorly understood, although it is now clear that they cannot be delineated under the simplistic paradigm of a balance of matrix anabolism versus catabolism. [1][2][3][4] Therefore, the discovery of new targetable disease mechanisms is essential to the design of effective biological therapies to complement existing strategies for osteoarthritis (OA) prevention in the clinic. With respect to post-traumatic OA, the cellular reaction to joint tissue injury can be viewed as a classical "wound-healing" response, involving a balance between "inflammatory/fibrotic" and "chondrogenic/osteogenic" pathways in the injured joint environment.…”
mentioning
confidence: 99%